This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: wei (jw35975) – HW1 – milburn – (54685) 1 This printout should have 24 questions. Multiplechoice questions may continue on the next column or page – find all choices before answering. 001 10.0 points Which, if any, of the following statements are true when a, b are real numbers? A. For all positive a and b . a − b √ a + √ b = √ a + √ b . B. For all a and b , radicalBig ( a + b ) 2 =  a + b  . C. For all positive a and b , √ a + b = √ a + √ b . 1. B and C only 2. none of them 3. B only correct 4. A only 5. all of them 6. A and C only 7. A and B only 8. C only Explanation: A. FALSE: by the known difference of squares factorization, x 2 − y 2 = ( x − y )( x + y ) . But if a, b are positive we can set x = √ a and y = √ b . Thus, after division, a − b √ a + √ b = √ a − √ b , contrary to the assertion. B. TRUE: we know that radicalBig ( x + y ) 2 =  x + y  , and since radicalbig ( · ) is always nonnegative, the right hand side has to be nonnegative. That’s why the absolute value sign is needed. C. FALSE: by the known product, ( x + y ) 2 = x 2 + 2 xy + y 2 . On the other hand, radicalBig ( x + y ) 2 =  x + y  , so if x + y > 0, x + y = radicalbig x 2 + 2 xy + y 2 . But if a, b are positive we can set x = √ a and y = √ b , in which case √ a + √ b = radicalBig a + 2 √ ab + b , contrary to the assertion. keywords: square root, properties of square root, PlaceUT, TrueFalse, T/F, 002 10.0 points Simplify the expression f ( x ) = 3 + 9 x − 4 1 + 15 parenleftBig x x 2 − 16 parenrightBig as much as possible. 1. f ( x ) = 3( x − 4) x + 16 2. f ( x ) = x + 4 x − 16 3. f ( x ) = 3( x + 4) 2 x + 16 wei (jw35975) – HW1 – milburn – (54685) 2 4. f ( x ) = 3( x + 4) x + 16 correct 5. f ( x ) = x − 4 x − 16 6. f ( x ) = x − 4 2 x − 16 Explanation: After bringing the numerator to a common denominator it becomes 3 x − 12 + 9 x − 4 = 3 x − 3 x − 4 . Similarly, after bringing the denominator to a common denominator and factoring it be comes x 2 − 16 + 15 x x 2 − 16 = ( x − 1)( x + 16) x 2 − 16 . Consequently, f ( x ) = 3 + 9 x − 4 1 + 15 parenleftBig x x 2 − 16 parenrightBig = 3 x − 3 ( x − 1)( x + 16) parenleftBig x 2 − 16 x − 4 parenrightBig . On the other hand, x 2 − 16 = ( x + 4)( x − 4) . Thus, finally, we see that f ( x ) = 3( x + 4) x + 16 . 003 10.0 points Let f be the quadratic function defined by f ( x ) = 2 x 2 − 12 x − 14 . Use completing the square to find h so that f ( x ) = 2( x − h ) 2 + k for some value of k . 1. h = 12 2. h = − 6 3. h = 3 correct 4. h = − 3 5. h = 6 Explanation: Completing the square gives f ( x ) = 2 x 2 − 12 x − 14 = 2( x 2 − 6 x − 7) = 2( x 2 − 6 x + 9 − 7 − 9) ....
View
Full
Document
This note was uploaded on 10/25/2011 for the course MATHEMATIC 408 taught by Professor Milburn during the Fall '11 term at University of Texas at Austin.
 Fall '11
 MILBURN
 Differential Calculus

Click to edit the document details